Application of Multi Layer Neural Network in Medical Diagnosis: an Efficient Survey - Rana, Arti; Singh Rawat, Arvind; Bahuguna, Himanshu; Bijalwan, Anchit (International Journal of Engineering and Technology, 2018)
A enormous extent of facts is presently accessible to medical proficient; diverge from information of medical signs to a assortment of varieties of biological facts as well as imaging machinesâ€™ results. All kind of facts gives statistics that which is assessed as well as allocated for exacting pathology throughout the investigative procedure. For restructuring the analytical procedure on a day-to-day basis practice and evade misdiagnosis, artificial intelligence techniques (artificial neural networks, computer aided diagnosis) are able to employ. These adaptive learning techniques could be hold different kinds of medicinal facts and amalgamate them into characterized outcomes.In this paper, we have concisely analyzed and deliberated about competencies, philosophy as well as restrictions of ANN in medicinal analysis concluded elected paradigms.Â Â